G-Protein Estrogen Receptor as a Regulator of Low-Density Lipoprotein Cholesterol Metabolism. Issue 1 (January 2015) - Hussain, Yasin; Ding, Qingming; Connelly, Philip W.; Brunt, J. Howard; Ban, Matthew R.; McIntyre, Adam D.; Huff, Murray W.; Gros, Robert; Hegele, Robert A.; Feldman, Ross D.
<x xml:space="preserve">Abstract</x> Objective— Estrogen deficiency is linked with increased low-density lipoprotein (LDL) cholesterol. The hormone receptor mediating this effect is unknown. G-protein estrogen receptor (GPER) is a recently recognized G-protein–coupled receptor that is activated by estrogens. We recently identified a common hypofunctional missense variant of GPER, namely P16L. However, the role of GPER in LDL metabolism is unknown. Therefore, we examined the association of the P16L genotype with plasma LDL cholesterol level. Furthermore, we studied the role of GPER in regulating expression of the LDL receptor and proprotein convertase subtilisin kexin type 9. Approach and Results— Our discovery cohort was a genetically isolated population of Northern European descent, and our validation cohort consisted of normal, healthy women aged 18 to 56 years from London, Ontario. In addition, we examined the effect of GPER on the regulation of proprotein convertase subtilisin kexin type 9 and LDL receptor expression by the treatment with the GPER agonist, G1. In the discovery cohort, GPER P16L genotype was associated with a significant increase in LDL cholesterol (mean±SEM): 3.18±0.05, 3.25±0.08, and 4.25±0.33 mmol/L, respectively, in subjects with CC (homozygous for P16), CT (heterozygotes), and TT (homozygous for L16) genotypes (P<0.05). In the validation cohort (n=339), the GPER P16L genotype was associated with a similar increase in LDL cholesterol: 2.17±0.05, 2.34±0.06, and 2.42±0.16 mmol/L, respectively, in subjects with CC, CT, and TT genotypes (P<0.05). In the human hepatic carcinoma cell line, the GPER agonist, G1, mediated a concentration-dependent increase in LDL receptor expression, blocked by either pretreatment with the GPER antagonist G15 or by shRNA-mediated GPER downregulation. G1 also mediated a GPER- and concentration-dependent decrease in proprotein convertase subtilisin kexin type 9 expression. Conclusions— GPER activation upregulates LDL receptor expression, probably at least, in part, via proprotein convertase subtilisin kexin type 9 downregulation. Furthermore, humans carrying the hypofunctional P16L genetic variant of GPER have increased plasma LDL cholesterol. In aggregate, these data suggest an important role of GPER in the regulation of LDL receptor expression and consequently LDL metabolism.